Assessment of heterosis and combining ability for fibre yield, its contributing and quality traits in Bt BGII upland cotton (Gossypium hirsutum L.) - S. S. Deshmukh1*, K. S. Baig2 and Bhaarat Sharma1 (Electronic Journal of Plant Breeding)
Heterosis breeding is one of the most practical and accomplishing tool for cotton improvement. In this context 32 intra-specific hybrids derived from eight lines and four testers were evaluated on multi-location to assess heterosis and combining ability for seed cotton yield and its contributing traits. Significant heterosis was observed in the crosses NH-2260 BGII x NH-2236 BGII, NH-2202 BGII x NH-2289 BGII and NH-2224 BGII x NH-2289 BGII for seed cotton yield and yield contributing characters over a better parent and best check. Combing ability analysis suggested the preponderance of non-additive gene action for most of studied traits. The line NH-2230 BGII and NH-2260 BGII were observed to be good general combiners for seed cotton yield and its contributing traits and the tester NH-2289 BGII was identified as the best general combiner for seed cotton yield and its contributing characters, ginning outturn, lint index. The hybrid NH-22105 BGII x NH-2236 BGII exhibited a significant positive SCA effect for seed cotton yield per plant.